Electrochemical and spectroelectrochemical characterization of newly synthesized manganese, cobalt, iron and copper phthalocyanines - KOCA, ATIF (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
Manganese, cobalt, iron, and copper phthalocyanines, tetra-substituted with 3,4-(dimethoxyphenylthio) moieties at peripheral positions, were synthesized and characterized by FT-IR, mass spectroscopy, and electronic spectroscopy. Electrochemical and spectroelectrochemical measurements exhibit that while copper phthalocyanine gives only ring-based electron transfer reactions, incorporating redox active metal centers, Co-II, (FeAc)-Ac-III, and (MnAc)-Ac-III, into the phthalocyanine core extends the redox richness of the phthalocyanine ring with the metal-based reduction and oxidation couples of the metal centers in addition to the common phthalocyanine ring-based electron transfer processes. In situ electrocolorimetric measurements of the complexes allow quantification of color coordinates of the each electrogenerated anionic and cationic redox species. Presence of O-2 in the electrolyte system influences the redox couples of the complexes due to the interaction between O-2 and metallophthalocyanines having redox active metal center. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Non-peripheral substitution; Thiol-substituted metallophthalocyanines; Iron; Manganese; Electrochemistry; Spectroelectrochemistry; IN-SITU; SUBSTITUTED PHTHALOCYANINES; ZINC PHTHALOCYANINES; METAL-FREE; ELECTROCATALYTIC ACTIVITY; HYDROGEN-PRODUCTION; CARBON-DIOXIDE; COMPLEXES; REDUCTION; ELECTROREDUCTION